Tendencias que afectan la auditoría de evaluación de desempeño en los cuerpos de bomberos de Ecuador. - Castillo Chávez, Irma Maricela (2022)
The performance evaluation in public administration, responding to a bureaucratic exercise, is directed towards an evaluation system for social results focused on public service, which revolves around the community. That is where lies the importance of reflecting on what are the trends that influence the evaluation to be objective, qualifying the performance of a server in the workplace, in institutional management and in the perception of users? As a case study, fire brigades, security and public order entities, which are regulated by COESCOP, have been selected. The particularity of these organizations lies in the autonomy to define their own evaluation procedure, since, at present, they are excluded from all regulations issued by the governing body on human talent in Ecuador, the Ministry of Labor. This research analyzes and describes how and what these trends are in the performance evaluation subsystem. It begins by specifying the lines of evaluation in the public sector, identifies the audit components in the performance evaluation subsystem, analyzes the current legal system applicable to these institutions and, finally, shows the conclusions and recommendations. For this, the grounded theory method was used.